Bacteriophage PBS2-induced inhibition of uracil-containing DNA degradation. - Katz, G E (1976)
Degradation of uracil-containing DNA by Bacillus subtilis extracts and its inhibition after infection by the uracil-containing DNA phage PBS2 have been investigated to resolve differences between the published reports of Tomita and Takahashi (1975) and Friedberg et al. (1975, 1976). The product of hydrolysis of PBS2 DNA, tritium labeled in its uracil and cytosine residues, is solely uracil and not deoxyuridine. The degrading activity is completely inhibited within 7 min after PBS2 infection, before any other known PBS2-induced protein is detectable. The production of the PBS2 inhibitor (a small, heat-stable protein) continues until 10 to 20 min postinfection.